Effect of lipids on the infectivity of influenza A viruses - Al-Dalawi, Lamyaa Mohammed (2019)
Influenza is an enveloped, single stranded negative sense RNA virus that subverts host cell factors like lipids for its own replication. Airway epithelium contributes towards the host defence against pulmonary pathogens by a number of mechanisms including the production of cytokines, chemokines and surfactant phospholipids and proteins. Phosphatidylcholine (PC) and phosphatidylglycerol (PG) make up the major of the composition of pulmonary surfactant. Therefore, this project aimed to explore the potential antiviral activity of exogenous phospholipids against influenza A viruses in vitro. The specific aims were to investigate the potential of these lipids to reduce the infectivity of influenza A virus and to measure the potential toxicity of specific exogenous phospholipids, using human adenocarcinomic alveolar basal epithelial (A549) and Madin Darby canine kidney (MDCK) cell lines and chicken red blood cells.